Age and Educational Level on Psychological Empowerment and Affective Commitment to Change - Mangundjaya, Wustari (Green Publisher, 2023)
Abstract: People cannot be separated from their characteristics, including age and education, as they are embedded in the person. These characteristics impact their personalities includinh their psychological empowerment, and attitudes toward change of the people in the organization. This research aims to identify the impact of age and educational level on affective commitment and psychological empowerment. The data were collected from 4 (four) local NGOs in Jakarta, with 113 respondents. The findings of the study revealed that age and educational level positively correlate with affective commitment to change, means that the older the people the higher their score on affective commitment. Further, the higher the level of education of people, the higher score of their affective commitment to change. Meanwhile, there is no significant relationship found between age and education with psychological empowerment. Results can be used for change management, especially in terms of choosing a change leader, which showed that the higher level of education and the older/senior people are more suitable to become the change leader, as they have higher score on affective commitment to change. However, this result cannot be generalized to all types of organizations as the results in various types of organizations were not consistent, and this result based on NGO organizations.